1996
DOI: 10.1007/bf02087914
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic detection of intestinal complications in Crohn's disease

Abstract: The aim of this study was to evaluate the sensitivity and specificity of ultrasound (US) in assessing the main abdominal complications of Crohn's disease (CD), such as strictures, fistulas and abscesses. A series of 98 consecutive inpatients with complicated and uncomplicated Crohn's disease, having undergone a complete endoscopic and radiographic evaluation of the intestinal tract, entered the study. In particular, in these patients the presence of strictures, fistulas, and abscesses, detected by means of col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
1
12

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(106 citation statements)
references
References 16 publications
3
90
1
12
Order By: Relevance
“…Within the last two decades, among the cross-sectional imaging techniques, the US has had a growing role in the development and application of techniques for the diagnosis of gastrointestinal diseases, such as appendicitis, diverticulitis and inflammatory bowel diseases (IBD) [12]. Today, bowel US is currently accepted as a clinically important first-line imaging technique in both patients with suspected CD and in follow-up patients known to have CD [13][14][15][16][17][18][19]. Furthermore, the introduction of oral contrast has improved the image quality, overall sensitivity and diagnostic accuracy in the detection of small bowel lesions in CD patients [20], and thus contrast-enhanced ultrasound (CEUS) has become an important imaging modality in patients with CD for grading of disease activity, differentiation between small bowel stricture due to inflammation or mural fibrosis, and the assessment of the response to specific therapy [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Within the last two decades, among the cross-sectional imaging techniques, the US has had a growing role in the development and application of techniques for the diagnosis of gastrointestinal diseases, such as appendicitis, diverticulitis and inflammatory bowel diseases (IBD) [12]. Today, bowel US is currently accepted as a clinically important first-line imaging technique in both patients with suspected CD and in follow-up patients known to have CD [13][14][15][16][17][18][19]. Furthermore, the introduction of oral contrast has improved the image quality, overall sensitivity and diagnostic accuracy in the detection of small bowel lesions in CD patients [20], and thus contrast-enhanced ultrasound (CEUS) has become an important imaging modality in patients with CD for grading of disease activity, differentiation between small bowel stricture due to inflammation or mural fibrosis, and the assessment of the response to specific therapy [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Using intra-operative findings as the reference standard, the authors found that ultrasound correctly identified all 22 of the patients with strictures and correctly excluded the presence of these lesions in 10 of 11 cases (sensitivity 100 %, specificity 91 %). The high diagnostic accuracy of ultrasound in this setting has been confirmed by Maconi et al [48], who reported a sensitivity of 74 % and specificity of 93 % for ultrasound detection of strictures, although, as they pointed out, the accuracy varied depending on the lesion's location (ileum vs. colon).…”
Section: Ultrasoundmentioning
confidence: 64%
“…The placement of the nasojejunal tube, necessary for the enteroclysis, is invasive, requires the use of ionizing of patients with CD [39,40] . and in early identifying intraabdominal complications, such as abscesses, fistulae and strictures [41][42][43][44] . The reported sensitivity of US in detecting CD strictures approximately is 74%-80% [41] .…”
Section: Cross Sectional Imagingmentioning
confidence: 99%